Sources of polycyclic aromatic hydrocarbons in South China Sea short core sediments off Southern part Terengganu, Malaysia and multivariate statistics approaches - Pang, Swee Yun; Suhaimi Suratman,; Hii, Yii Siang; Simoneit, Bernd R.T.; Norhayati Mohd Tahir, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Sediment cores from the southern South China Sea off the Terengganu coast were analyzed for polycyclic aromatic hydrocarbons (PAHs) and perylene. The concentrations of total 17 PAH (TPAHs) and perylene varied between 5.45-27.7 ng/g and 0.51-7.77 ng/g, respectively. Analyses of variance showed significant differences between the stations, but not in sub-bottom depths at the 0.05 level. The PAH cross plots showed a predominance of pyrogenic over petrogenic PAHs. Principal component analysis (PCA) showed clustered PAHs that are correlated with total organic carbon (TOC), indicating the importance of surface runoff via fluvial transport for contributing these PAHs to the coastal environment of the study area. Overall, the concentrations of PAHs in the study area are considered to be in the low range, not exceeding the 100 ng/g mark.